RNA Synthesis in Yersinia pestis During Growth Restriction in Calcium-Deficient Medium - Charnetzky, Willard T. (1982)
Yersinia pestis requires 2.5 mM Ca(2+) for growth at 37°C but not at 26°C. After a shift from 26 to 37°C in a Ca(2+)-deficient medium, an ordered series of metabolic alterations occur which result in transition from a growing cell to a viable but non-proliferating cell. The earliest known alteration in normal metabolism associated with this transition is a termination of net RNA synthesis. Competitive RNA/DNA hybridizations with uniformly labeled RNA and stable RNA competitor indicated identical mRNA to stable RNA ratios in growing cells and non-proliferating Ca(2+)-deprived cells. Similar hybridizations with pulse-labeled RNA demonstrated that growing cells synthesized 57% mRNA, 37% rRNA, and 5% tRNA, whereas Ca(2+)-deprived cells synthesized 95% mRNA, 4.7% rRNA, and 0.7% tRNA. After addition of radioactive uracil and rifampin to growing and Ca(2+)-deprived cells, decay of approximately 40 and 90% of the newly synthesized RNA was found for growing and Ca(2+)-deprived cells, respectively. The half-life of the mRNA was found to be 1.5 min for growing cells and 4.5 min for Ca(2+)-deprived cells. Y. pestis elicited increases in the levels of guanosine tetraphosphate and guanosine pentaphosphate in response to amino acid deprivation and yielded transient increases in the levels of these phosphorylated nucleotides after a shift from 26 to 37°C. These increases were independent of Ca(2+) availability and preceded the alteration in RNA synthesis by more than 1 h. The levels of these phosphorylated nucleotides then stabilized at about 80 and 40 pmol for Ca(2+)-deprived and Ca(2+)-supplemented cultures, respectively, and did not increase further in the Ca(2+)-deprived culture at the time corresponding to the reduction in stable RNA synthesis. These findings indicate that the early lesion in RNA synthesis associated with the growth restriction of Ca(2+)-deprived Y. pestis reflects a block in stable RNA synthesis and that this effect is not mediated by guanosine tetraphosphate or guanosine pentaphosphate.